2016
DOI: 10.1016/j.apjtm.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of skin rash in dengue fever: A focus on discomfort, complications, and disease outcome

Abstract: Cutaneous manifestations provide an important clue to dengue fever. In patients with dengue fever, those with skin rash tend to have itching and swelling of the palms/soles, however, those without skin rash tend to have more complications and poor disease outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…In contrast to the site of initial virus infection, areas of skin with pathologic manifestations during the acute systemic stage of disease, which may be characterized by haemorrhaging or oedema, are usually not positive for DENV infection and, thus, these lesions are likely to be the result of the systemic inflammatory response [16]. Surprisingly, in one study, the early presence of rash or cutaneous manifestations of disease was associated with improved disease outcomes in human patients [17]. However, other studies noted that immune cells in the skin were activated at the onset of DSS [18], potentially reflecting the systemic inflammatory response.…”
Section: Initiation Of Natural Route Infection Through the Skinmentioning
confidence: 99%
“…In contrast to the site of initial virus infection, areas of skin with pathologic manifestations during the acute systemic stage of disease, which may be characterized by haemorrhaging or oedema, are usually not positive for DENV infection and, thus, these lesions are likely to be the result of the systemic inflammatory response [16]. Surprisingly, in one study, the early presence of rash or cutaneous manifestations of disease was associated with improved disease outcomes in human patients [17]. However, other studies noted that immune cells in the skin were activated at the onset of DSS [18], potentially reflecting the systemic inflammatory response.…”
Section: Initiation Of Natural Route Infection Through the Skinmentioning
confidence: 99%
“…In a recent study, the disease course and complications in patients with skin rash were not found to be worse than patients who did not have skin rash. On the other hand, more hemorrhagic manifestations, genital mucosal involvement, and higher incidence of platelet transfusion were noted in patients without skin rash …”
mentioning
confidence: 97%
“…Its major vector is the mosquito Aedes aegypti. Clinical manifestations of DF vary from a mild self‐limiting illness to severe and fatal forms like dengue hemorrhagic fever and dengue shock syndrome …”
mentioning
confidence: 99%
See 2 more Smart Citations